Messiaen: Quatuor pour la fin du Temps - Pople, Anthony (Cambridge Cambridge University Press, 1998)
This book is about one musical work, the popular Quartet for the End of Time by the great French composer Olivier Messiaen. Like virtually all of his works, the Quartet combines the striking technical achievement of Messiaen's rich and attractive musical style with a deeply felt theological inspiration. Anthony Pople's book provides an introduction to Messiaen's style through an examination of this great work, showing how it came to be composed while Messiaen was a prisoner-of-war and premiered under extraordinary conditions in Stalag VIIIA in 1941. He gives an in-depth assessment of each of its eight movements